Identifikasi mineral magnetik menggunakan metoda X-Ray Diffraction (XRD) Terhadap Polusi di Kota Padang - Catur Krisna Gobah (PILLAR OF PHYSICS, 2016)
Many industrial processes such as the production of steel and cement, generate airborne magnetic material. That Particle to contained organized as magnetic mineral included kind of iron sulfide mineral and iron titanium sulfide. Industrial process using as a power plant in that process. Before being burned, coal is essentially nonmagnetic. The process of combustion causes the pyrite present dissociate and form pyrrhotite  and sulfur gas. Above about 1350 K, pyrrhotite decomposes into sulfur and iron. Spherical iron particles are formed and subsequently oxidize to magnetite. This research intent on determine level of pollution and kind of magnetic mineral in a pollutant of padang city by undertaking measuring value of magnetic suseptibilty. By assume topsoil as a pollutant collector, so making use topsoil as a sample in this research. Measuring value of magnetic suseptibility by using magnetic suseptibilitymeter . Then identification kind of magnetic mineral by using a  X-Ray Diffractometer (XRD). Data prosessing output of XRD organized as chart for know the kind of magnetic mineral. Data output from measuring value of magnetic suseptibility for know the pollution levels. Result of this research  magnetic mineral has present in the Padang city magnetite is a big part. Hematite is a other mineral magnetic omly one sample contained that magnetic mineral just in sample KTT 06this sample taking at Lubuk Buaya, Koto Tangah subdistrict.